2020
DOI: 10.1080/21645515.2020.1729027
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of rubella among pregnant women in Sub-Saharan Africa: a meta-analysis

Abstract: Background: Rubella continues to be a leading cause of vaccine-preventable congenital birth defects and permanent organ damage, especially in developing countries. For women who are infected with the rubella virus (RV) before conception or during the first trimester of pregnancy, the unborn child has up to a 90% probability of developing congenital rubella syndrome. There are limited data on the seroprevalence of the rubella virus among pregnant women in Sub-Saharan Africa. Therefore, the aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
1
Order By: Relevance
“…The seroprevalence of rubella IgM among pregnant females in this study was 1.2%. This is lower than findings from other countries like Ethiopia (9.5%), Nigeria (9.2%), Sub‐Saharan Africa (5.1%) and Turkey (2%) 1,11 . These differences between the seroprevalence of rubella IgM in this study and others could be explained by the variations in the rubella virus endemicity and the vaccination programs between countries 1 .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The seroprevalence of rubella IgM among pregnant females in this study was 1.2%. This is lower than findings from other countries like Ethiopia (9.5%), Nigeria (9.2%), Sub‐Saharan Africa (5.1%) and Turkey (2%) 1,11 . These differences between the seroprevalence of rubella IgM in this study and others could be explained by the variations in the rubella virus endemicity and the vaccination programs between countries 1 .…”
Section: Discussioncontrasting
confidence: 82%
“…and Turkey (2%). 1,11 These differences between the seroprevalence of rubella IgM in this study and others could be explained by the variations in the rubella virus endemicity and the vaccination programs between countries. 1 The lack of association between sociodemographic and antenatal characteristics with positive rubella IgM in this study has also been found in various previous studies.…”
Section: Discussionmentioning
confidence: 53%
“…In children, the percentages ranged from 99.2% to 63.6% [12]. In a metaanalysis of 28 studies in Sub-Saharan countries, the pooled seroprevalence of anti-rubella IgG among pregnant women was found to be about 89.0% (95% CI: 84.6-92.3%), and for rubella IgG and IgM, the pooled prevalence among pregnant women was 5.1% (95% CI: 2.6-9.9) [17].…”
Section: Discussionmentioning
confidence: 99%
“…2014) and have conducted serological surveys to determine the proportion of women of childbearing age who are susceptible to rubella. (Kassa ZY et al, 2020). Rubella is a public health problem that results in the birth of approximately 110,000 children with congenital rubella syndrome (CRS) (Duszak, RS et al, 2009).…”
Section: Introductionmentioning
confidence: 99%